Is Online Health Information a Threat?—Untangling the Longitudinal Associations Among Health Information Scanning, Seeking, and Risk Perceptions - Zheng, Han (Risk analysis, 2025)
In today's algorithm‐driven era, individuals not only actively seek health information through search engines or health websites but also passively encounter health‐related content while browsing social media feeds. These two distinct behaviors (i.e., intentional information seeking and incidental information scanning) may each contribute to individuals’ perceptions of health risks. A substantial body of work has examined the relationship between online health information behaviors (e.g., seeking) and risk perceptions across various contexts. However, the findings on the directionality of these relationships remain equivocal. Drawing on the literature on health information acquisition, this study investigates the longitudinal associations among online health information seeking, scanning, and risk perceptions. Data from a three‐wave panel survey with 654 participants indicate that health information scanning and seeking exhibit a stable, reciprocal relationship over time. Moreover, information seeking is positively associated with risk perceptions across waves, whereas information scanning does not exert a direct effect. These findings contribute to theoretical developments in digitally mediated risk communication by highlighting the temporal dynamics and interplay of online information behaviors. They also offer practical guidance for designing more targeted and psychologically informed digital health communication strategies.